2002
DOI: 10.1038/sj.mp.4001101
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory region variability in the human presenilin-2 (PSEN2) gene: potential contribution to the gene activity and risk for AD

Abstract: We have analyzed the 5Ј-upstream promoter region of the presenilin 2 gene (PSEN2) for regulatory elements and examined Alzheimer disease (AD) patients and non-demented individuals for polymorphisms in the 5Ј upstream promoter region of the PSEN2 gene. Direct sequencing analysis detected a common single adenine (A) nucleotide deletion polymorphism in the upstream promoter region of the PSEN2 gene. Examination of cohorts of AD patients and agematched control individuals revealed no statistically significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…This strategy results from two major observations: (i) the expression of numerous genes is modified during AD aetiology, [4][5][6][7][8] (ii) polymorphisms within promoters of the APOE, PS1, PS2 and APP genes have been associated with the occurrence of AD. [9][10][11][12] Consequently, we assumed that genes located in one of the loci of interest defined by previous genome scans and exhibiting a differential expression between patients and controls, could constitute potential candidate genes for AD. We applied our strategy to nine different chromosomal regions previously identified by genome scan studies 13 and selected a candidate gene expressed in cases but not in controls, the ornithine transcarbamylase (OTC) located on Xp21.1.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy results from two major observations: (i) the expression of numerous genes is modified during AD aetiology, [4][5][6][7][8] (ii) polymorphisms within promoters of the APOE, PS1, PS2 and APP genes have been associated with the occurrence of AD. [9][10][11][12] Consequently, we assumed that genes located in one of the loci of interest defined by previous genome scans and exhibiting a differential expression between patients and controls, could constitute potential candidate genes for AD. We applied our strategy to nine different chromosomal regions previously identified by genome scan studies 13 and selected a candidate gene expressed in cases but not in controls, the ornithine transcarbamylase (OTC) located on Xp21.1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an insertion/deletion polymorphism (A,ÀA) in the upstream promoter region of the PSEN2 (presenilin 2) gene, when homozygous (ÀA/ÀA), has been suggested to increase the risk for Alzheimer disease; DNA-protein binding analysis experiments suggested that this site interacts with a TF. 26 An SNP in the human SCGB3A2 (secretoglobin, family 3A, member 2) promoter that regulates transcription was reported associated with asthma, 27 and an SNP in the promoter of the human UCP2 (uncoupling protein 2 (mitochondrial, proton carrier)) was reported to be associated with risk of obesity. 28 Several polymorphisms have been described in the 5 0 -UTR of HTR1B, namely, GÀ511T,…”
Section: Introductionmentioning
confidence: 99%
“…For example, functional polymorphisms within the promoter sequences of APOE, PS1 and PS2 genes are associated with an increased risk of developing AD. [2][3][4] A similar involvement of the APP gene has been discussed. 5 Consequently, we have argued that genes exhibiting a differential expression between cases and controls, and located in one of the loci of interest defined by previous genome scans, could constitute potential candidate genes for AD.…”
Section: Introductionmentioning
confidence: 81%